Design Android-Based Car Rental Management Application Using Prototype Method - Naufal Fikri Aulia; Feri Candra (International Journal of Electrical, Energy and Power System Engineering, 2023)
Inayah's car rental is one of the business sectors in the field of transportation services at Pekanbaru, Riau. Inayah car rental carries out management activities for car rental management that can be rented from daily to monthly. Management of rental transactions is currently done manually by recording customer data and storing customer guarantees in the archives that have been provided. Problems arise when the data is lost or damaged while the car is on the customer's side. In addition, other issues arise when a customer cancels suddenly on that day, or the customer's uncertainty about car rental will impact other customers who are serious about renting a car at that time. From these problems, we need a system that can automatically manage, store, and manage car rental transactions using Android. The development method in this study uses the prototype development method. The Prototype is a development method that involves users in system development. Based on the research results, we get a very good interpretation of the standard quality of the ISO 25010 system test, functional, performance, reliability, maintainability, security, usability, and efficiency.